Dynamic threshold and quality meter based routing for cooperative broadband wireless networks - Chong, Eng Tan; Ee, Keng Tan (IEEE, 2009)
One of the important aspects to deal with in ad hoc cooperative wireless network is the mobility nodes. In ad hoc wireless networks, the nodes themselves are responsible for the routing and forwarding of packets. Hence, nodes of these networks function as routers that discover and maintain routes to other nodes in the same network as well as regular hosts. Frequent changes in the network topology require huge communication overhead in order to establish new routes and thus slowing down the communication or causes packet losses. In this paper, we proposed Channel State Information (CSI) based routing scheme for ad hoc cooperative wireless networks. The proposed approach will apply dynamic threshold and quality meter to improve the wireless channel quality of all available ad hoc nodes over the cooperative network and making sure that the conventional TCP will still be effective. The proposed scheme takes into consideration of choosing the best route on the fly for successful packet delivery while minimizing errors over the network.